Factors affecting habitat use of asian elephants for the buffer zone management and conservation of Huai Kha Khaeng World Heritage site, Thailand - Sangsan Phumsathan; Kittisak Thongwijit; Achara Simcharoen; Warong Suksavate; Ekaphan Kraichak; Andaman Chankhao; Nantachai Pongpattananurak (Global Ecology and Conservation)
Asian elephants in Thailand face threats from anthropogenic activities such as foraging for non-timber forest products (NTFP), livestock ranching, and expansion of agricultural areas. These threats to their habitats lead to human-elephant conflicts (HEC) and endanger the survival of Asian elephants. This study assesses seasonal changes in elephant densities by comparing habitats inside and outside a protected area and analyzing the impact of human activities on elephant habitat use in a buffer zone of the Huai Kha Khaeng World Heritage Site. We surveyed elephant densities using 130 sample plots, employing the dung count method and categorizing surveyed plots by forest types, environmental factors, and anthropogenic activities. Surveys conducted seven times (from October 2018 to September 2019) captured seasonal changes in NTFP, livestock ranching, and agricultural activities. Anthropogenic activities affecting elephant habitat use were examined using a mixed-effect model. Seasonal variations significantly impacted elephant densities across surveys, averaging 0.63 individuals/km². High densities (1.05–1.27) occurred outside the protected area in the dry season while lower densities (0.09–0.36) were recorded in the rainy season. During April-May and October-November, elephants favored areas with NTFP utilization, coinciding with villagers' foraging periods, potentially intensifying HEC. Elephants avoided buffer areas with intense livestock activity from the late dry season to the end of the rainy season but favored open areas, crop fields, and fruit orchards during the dry season. Recommendations include strict enforcement to remove livestock, implementing seasonal guidelines for NTFP harvesting, and prioritizing wildlife habitat management within the protected area. These measures are crucial for mitigating human-elephant conflicts, conserving elephant habitats, and fostering coexistence between local communities and elephants in the buffer zones of the world heritage site.